Analisis Yuridis Perlindungan Hukum atas Sertipikat Pengganti Berdasarkan Keterangan Palsu: Studi Putusan No. 450/Pid.B/2022/PN.Smn - Sianipar, Geofanny Guruh Hasintongan; Yamin, Muhammad; Sembiring, Rosnidar (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the legal protection afforded to holders of Land Ownership Certificates who are harmed by the issuance of replacement certificates based on false statements, as reflected in Decision Number 450/Pid.B/2022/PN Smn by the Sleman District Court. The research adopts a normative juridical method with a descriptive-analytical approach through literature study and qualitative analysis. The findings indicate that a replacement certificate issued based on a false loss report has no legal validity and may be annulled. In this case, the judge rendered an appropriate decision by sentencing the perpetrator to 1 year and 2 months of imprisonment under Article 266 paragraph (1) of the Indonesian Penal Code, and ordered the return of the replacement certificate to the local Land Office for proper administrative processing. The theoretical implication of this research underscores the importance of legal protection for rightful landowners and the need to strengthen verification mechanisms in the issuance of replacement certificates to prevent legal abuse by irresponsible parties.